A Try to combine more than approaches and competitive strategies to achieve a sustainable competitive advantage. - Larbi, GHOUZI Mohamed (Journal of Economics and Administrative Sciences, 2019)
The objective of this research paper is two-fold. The first is a precise reading of the theoretical underpinnings of each of the strategic approaches: "Market approach" for (M. Porter), and the alternative resource-based approach (R B V), advocates for the idea that the two approaches are complementary. Secondly, we will discuss the possibility of combining the two competitive strategies: cost leadership and differentiation. Finally, we propose a consensual approach that we call "dual domination".